Transjugular intrahepatic portosystemic shunt in the treatment of portal vein thrombosis: a critical review of literature - Qi, Xingshun (Hepatol Int, 2011)
Reports of successful transjugular intrahepatic portosystemic shunt (TIPS) surgery in patients with portal vein thrombosis (PVT) are considered anecdotal owing to the technical difficulty of the procedure and potential procedure-related complications. A literature review was undertaken to determine the feasibility and safety of TIPS in the treatment of PVT. All studies in which TIPS was attempted in patients with PVT were identified by searching through the PUBMED and MEDLINE databases. A total of 424 PVT patients undergoing TIPS were reported in 54 articles. The success rate of TIPS insertion was 67–100% in 19 case series. Further, 85 patients with portal cavernoma underwent successful TIPS insertions. Three therapeutic strategies of TIPS placement were used: (1) TIPS placement followed by portal vein recanalization via the shunt, (2) portal vein recanalization via percutaneous approaches followed by TIPS placement, and (3) TIPS insertion between a hepatic vein and a large collateral vessel without portal vein recanalization. Four approaches were used to access the portal vein: transjugular, transhepatic, transsplenic, and transmesenteric. Intra-abdominal hemorrhage secondary to hepatic capsule perforation was lethal in only three patients. No episode of pulmonary embolism was reported. Other procedure-related complications were reversible. The overall incidence of shunt dysfunction and hepatic encephalopathy was 8–33% and 0–50%, respectively. In conclusion, the reviewed studies uniformly support the feasibility and safety of TIPS for PVT even in the presence of portal cavernoma. Further, several major issues that remain unresolved are discussed.